A Case Report of Cardiofaciocutaneous Syndrome with MAP2K1 Pathogenic Variant - Tang Q; Gong D; Ye XM; Xu JR; Yang YC; Yan LJ; Zou L; Wen XL (Dove Medical Press, 2023)
Qiong Tang, Dai Gong, Xiao-Min Ye, Jun-Ru Xu, Yi-Can Yang, Li-Juan Yan, Li Zou, Xiang-Lan Wen Department of Children Health Care Center, Zhuzhou Hospital Affiliated to Xiangya Medical College, Central South University, Zhuzhou, People's Republic of ChinaCorrespondence: Xiang-Lan Wen, Department of Children Health Care Center, Zhuzhou Hospital Affiliated to Xiangya Medical College, Central South University, No. 116 of Changjiang South Road, Tianyuan District, Zhuzhou City, Hunan Province, 412007, People's Republic of China, Tel +86 13873317331, Email wenxianglianwxl@126.comAbstract: Craniofacial dysmorphism, cardiac abnormalities, ectodermal abnormalities, psychomotor delay, intellectual disability, and short stature are all hallmarks of the extremely rare disorder known as cardiofaciocutaneous syndrome (CFCS). Although CFCS is considered rare, approximately 300 cases have been documented in the literature. In this report, we discuss a patient diagnosed with CFCS without the typical heart malformations but with craniofacial features, skin abnormalities, intellectual disability, and short stature. Genetic testing revealed the presence of three potentially harmful variants: one in the MAP2K1 gene and two in the ATP2B3 and CDC42BPB genes, the significance of which is currently not yet found. Our findings in this case report suggest that the clinical symptoms of CFCS may be atypical, thereby expanding our understanding of the symptom spectrum of the disease. Simultaneously, the link between the clinical symptoms of the patient and the two unknown pathogenic variants has not been established. This case report supplements existing clinical reference material by providing valuable insights into the specific scenario.Keywords: cardiofaciocutaneous syndrome, gene detection, intellectual disability, neurodevelopmental syndrome, short stature, spinocerebellar ataxia